Pattern of adverse drug reactions due to antibiotics in a tertiary care hospital - Akalu, Suchitra D.; Belavadi, Niveditha G. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Adverse reactions are known to occur with all classes of drugs and the incidence of adverse drug reactions (ADRs) due to antibiotics has increased with rise in infectious diseases contributing significantly to the increased health care costs. Methods: This retrospective observational study analysed the ADRs due to antibiotics that were reported by spontaneous reporting to ADR monitoring centre (AMC), functioning from Department of Pharmacology, ESIC-MC and PGIMSR. The total study period was 48 months from January 2013 to December 2016. During this period, all the ADRs due to antibiotics reported to the AMC were included in the study. This study analysed the retrospective data to find out the pattern of adverse drug reactions due to antibiotic drug class. Causality, severity and preventability were assessed using standard scales. Results: During the study period, a total of 228 ADRs due to antibiotic use were reported among 179 patients. Gender-wise distribution showed that males were slightly more affected than females by the ADRs due to antibiotics [93(52%) Vs. 86 (48%)]. Out of the total 179 antibiotics administered to the patients, beta-lactam antibiotics dominated followed by nitroimidazoles, quinolones and glycopeptide antibiotics in causing ADRs. Rashes and itching were most common ADRs followed by breathlessness and hypotensive episodes. Causality was assessed by Naranjo algorithm scale and causality was definite in 16 (7%), probable in 87 (38%) and possible in 125 (55%). Severity of the ADRs was assessed by Hartwig and Siegel scale and it was found that most of the ADRs 198 (87%) were of mild severity and 30 (13%) were of moderate severity and none of them were severe or lethal. Preventability was assessed by Schumock and Thornton scale and it was found that only 24 (11%) were preventable, 74 (32%) were probably preventable and 130 (57%) were not preventable. Conclusions: The study concluded that ADRs due to antibiotics are common and few of them resulted in increased healthcare cost due to the need for some interventions and increased length of hospital stay. The health system should promote the spontaneous reporting of ADRs due to antibiotics, proper documentation and periodic reporting to regional pharmacovigilance centers to ensure drug safety.